The extent to which ‘place’ has an impact upon student outcomes in a Nottinghamshire secondary school - Tuck, Oliver (2017)
This paper investigates how place/location has an impact upon how students achieve in one Nottinghamshire Secondary school. School-based data and neighbourhood statistics were used, alongside qualitative interviews and a survey of selected year 8 students, to develop an understanding of how students’ geographic location affects their school outcomes. More importantly, the concept of ‘place’ was explored beyond its geo-political definition, to ascertain the extent to which ideas of ‘place’ also have an impact on school outcomes. It is argued that there are some clear links between the economic status of the family, and the location of students. Furthermore, the overarching findings demonstrate that students held a narrow conception of ‘place’, and thus the largest influence on their educational outcomes come from the family home itself.